Group velocity estimation of Rayleigh wave of crust and upper mantle based on the broadband seismic data in Vietnam East Sea - Tien, Hung Nguyen; Thi, Giang Ha; Le, Minh Nguyen; Tanaka, Satoru; Ishihara, Yasushi; Vinh, Long Ha; Quang, Khoi Le (Vietnam Journal of Marine Science and Technology, 2017)
In this study, the Rayleigh wave group velocity (Vgr) of Vietnam East Sea is determined by using 36,195 broadband velocity seismograms recorded by 95 seismic stations from 381 events with magnitude larger than 6.0, depth lower than 100 km, from 2000 to 2016 and applying the multiple filter analysis, integrated into Computer Program Seismology (CPS) by Herrmann and Ammon (2002). Using 2,600 high quality dispersion curves of Vrg passing through the Vietnam East Sea, the results show that: (i) The dispersion curves of Vgr in the continent region have the function graph of grade 3 with a minimum (at Vrg ≈ 2.8 km/s; T = 20 - 26 s) and a maximum (at Vrg ≈ 3.9 km/s; T = 50 - 90 s) and the dispersion curves of Vgr in the ocean have the function graph of grade 2 with a maximum (≈ 3.9 km/s; T = 40 - 90 s); (ii) At the period lower than 40s, the Vrg in Vietnam East Sea is from 2.8 km/s to 4.0 km/s and reaches a maximum at the center area; (iii) At the period over 50s, the Vrg in Vietnam East Sea is from 3.2 km/s to 4.2 km/s and the low Vgr area appears along the Red river, Con Co island, Dai Loan island, Visayas, Philippines and Borneo island.